Les apports de la sociologie du genre à la critique du travail - Elsa Galerand; Danièle Kergoat (La Nouvelle Revue du Travail)
Having analysed the different currents populating the sociology of gender and specified any continuous or discontinuous ties to the sociology of work, Elsa Galerand and Danièle Kergoat try demonstrate how the current of materialist feminism has renovated the sociology of work and asked particular questions of it, whether conceptually or in terms of analytical objects and fields. Ever since domestic work was re-theorised to achieve a more extensive redefinition of the concept of work – including a conceptualisation of sexualised social relations and the sexual division of labour – what must ultimately be revealed is this kind of sociology’s critical and subversive potential.